Métodos para determinar la configuración absoluta de una molécula - Cedrón, Juan Carlos (2008)
Methods for the assignment of the absolute configuration of an organic molecule: The assignment of the absolute configuration of chiral molecules represents a great challenge for organic chemists. There are several techniques in order to establish it, and they are described in this work, as well as examples of how they can be applied in the assignment of the absolute configuration of natural products.